2019
DOI: 10.7717/peerj.7552
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic habitat and the coral microbiomes of urban-impacted reefs

Abstract: Coral reefs are in decline worldwide. In response to this habitat loss, there are efforts to grow, outplant, and restore corals in many regions. The physical oceanographic habitat of corals—such as sea temperature, waves, ocean currents, and available light—is spatially heterogeneous. We therefore hypothesize that outplant location may affect microbiomes, and ultimately, coral health and restoration success. We evaluated the influence of the physical oceanographic habitat on microbes in wild Porites astreoides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…One study identified five bacteria families associated with SCTLD lesions, but none were found across all four coral species examined . Coincident with the initial outbreak of SCTLD, a dredging project at the Port of Miami in 2013-2015 increased sedimentation (Miller et al, 2016;Cunning et al, 2019) and relative turbidity (Rosales et al, 2019) in adjacent reefs. This has led to a controversial hypothesis that sediment is a potential source of transmission of the SCTLD pathogen(s) (Miller et al, 2016;Cunning et al, 2019;Gintert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One study identified five bacteria families associated with SCTLD lesions, but none were found across all four coral species examined . Coincident with the initial outbreak of SCTLD, a dredging project at the Port of Miami in 2013-2015 increased sedimentation (Miller et al, 2016;Cunning et al, 2019) and relative turbidity (Rosales et al, 2019) in adjacent reefs. This has led to a controversial hypothesis that sediment is a potential source of transmission of the SCTLD pathogen(s) (Miller et al, 2016;Cunning et al, 2019;Gintert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While ships clearly have the potential to spread pathogens, understanding the likelihood of ship-mediated spread of SCTLD remains challenging given the unknown etiology of the disease. While successful treatment with antibiotics suggests the pathogen(s) may be bacterial ( Aeby et al, 2019 ; Neely et al, 2020 ), we cannot rule out a possible role of free-living or bacteria-infecting viruses, other microorganisms ( Rosales et al, 2020 ), or water quality ( Miller et al, 2016 ; Cunning et al, 2019 ; Rosales et al, 2019 ). Additionally, the potential that SCTLD is caused by a consortium of pathogens complicates development of targeted tests or treatments.…”
Section: Consideration and Future Researchmentioning
confidence: 98%
“…In these areas, unique combinations of environmental factors can lead to outcomes that are difficult to predict using single-taxon, single-stressor studies. Particularly persistent coral species or genotypes may reveal mechanisms of resilience in the genetics of the coral host and/or the associated algal symbionts of the family Symbiodiniaceae 8 , as well as the wider microbiome 9 . These natural associations and molecular mechanisms may ultimately prove useful for increasing the efficacy and efficiency of restoration efforts and are likely critical for maintaining ecosystem function in a rapidly changing world.…”
Section: Introductionmentioning
confidence: 99%